Uptake of HO2 radicals on Arizona Test Dust - Y. Bedjanian; M. N. Romanias; A. El Zein (Atmospheric Chemistry and Physics, 2013)
The interaction of HO2 radicals with solid films of Arizona Test Dust (ATD) was studied using a low-pressure flow reactor (1–9 Torr) combined with a modulated molecular beam mass spectrometer for monitoring of the gaseous species involved. The reactive uptake coefficient of HO2 was measured from the kinetics of HO2 consumption on Pyrex rods coated with ATD as a function of HO2 concentration ((0.35–3.30) × 1012 molecule cm−3), relative humidity (RH = 0.02–94%), temperature (T = 275–320 K) and UV irradiance intensity (JNO2 = 0–0.012 s−1). The initial uptake coefficient was found to be independent of concentration of HO2, temperature and irradiation conditions, and to decrease with increasing relative humidity: γ0 = 1.2/(18.7 + RH1.1) (with 30% estimated conservative uncertainty). The uptake coefficient was calculated using geometric surface area and should be considered as an upper limit of γ0. An upper limit of 5% was found for the gaseous H2O2-forming pathway of the HO2 reaction with ATD surface. The results of the measurements indicate that HO2 loss on dust aerosol may be a non-negligible sink for HOx species in the troposphere with the effect depending on specific local conditions.